Surveillance for CRC in Patients With IBD - Nichols, Emma Hitt (MD Conference Express, 2015)
Patients with inflammatory bowel disease are at an increased risk of developing colorectal cancer. These patients should undergo surveillance colonoscopy for detection of dysplasia or adenoma. Studies have demonstrated that chromoendoscopy is the most effective technique for detection of dysplasia in this population.